To evaluate the role of double J stent versus no stent in patients of renal and upper ureteric calculus undergoing extracorporeal shock wave lithotripsy - Shirale, Vaishali; Jain, Sudhir Kumar; Kaushik, Rohit (Asian Journal of Medical Sciences, 2022)
Background: Extracorporeal shock wave lithotripsy (ESWL) was first introduced by Chaussy in 1980 for the treatment of urolithiasis, which has revolutionized the treatment of urinary stones. Renal colic, urinary tract obstruction, uremia, and renal failure can occur because of the stone fragments obstructing the ureter during the post-ESWL period. The role of double-J (DJ) stents in ESWL is controversial. Aims and Objectives: The aim of the study was to evaluate the role of DJ stent in patients with renal and upper ureteric calculus undergoing extracorporeal shockwave lithotripsy. Materials and Methods: Two hundred patients with solitary calculus 5 mm–2 cm in size, amenable to ESWL, located in renal pelvis, upper or middle calyx, upper ureter visiting Lok Nayak Hospital, New Delhi from December 2015 to April 2019 were studied and randomized into two groups: Test group (non-stented, 100 patients) and control group (Stented, 100 patients). Both groups underwent ESWL and subsequently compared for the following parameters: Stone clearance, post lithotripsy pain and analgesic dose requirement, number of ESWL sittings and shockwaves required, steinstrasse, urinary tract infection (UTI), and hematuria. Patients were followed up for 3 months after stone clearance to look for any recurrence. Results: There was a significant difference (P<0.05) in the two groups with smaller number of ESWL sittings and number of shockwaves required, low frequency of colicky pain episodes and mean pain score, less analgesic dose requirement, lower incidence of hematuria, and UTI in non-DJ stent group. The overall stone clearance was higher in the non-DJ stent group (96.4%) as compared to the DJ stent group (89.3%). The incidence of steinstrasse was higher in the DJ stent group (10.7%) as compared to none in the non-DJ stent group. Conclusions: There is no additional benefit of DJ stent on stone clearance, rather stenting further increases the morbidity due to associated complications. DJ stenting should not be performed in patients undergoing ESWL for renal and upper ureteric calculus up to 2 cm size.